Immunogenic dying cells elicit potent anti-tumor T cell immunity against lung metastasis and tumorigenesis - Min Hu; Xinyu Meng; Tong Wang; Yifan Wang; Xiaodong Chen; Dongliang Xu; Wei He; Hongjia Zhang; Wenzheng Guo; Bo Jing; Siwei Zhang; Jianhua Xu; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Immune checkpoint blockades (ICBs) are promising, however they do not fit all types of tumor, such as those lack of tumor antigens. Induction of potent anti-tumor T cell immunity is critical for cancer therapy. In this study, we investigated the efficacy of immunotherapy via the immunogenic cell death (ICD) dying tumor cells in mouse models of lung metastasis and tumorigenesis. Methods ICD was induced by short exposure to lethal dose of chemotherapeutic drug doxorubicin (Dox), which initiated an irreversible ICD program in tumor cells. We immunized mice with ICD dying tumor cells in prevention, therapy in lung metastasis models, and Gprc5a-knockout (ko) model of lung tumorigenesis. T cells and macrophages isolated from lymph nodes or tumor tissues were analyzed by flow cytometry. Cytokines were analyzed by ELISA or Q-PCR analysis. Results Immunization with these live but ICD dying tumor cells induced potent tumor-specific anti-tumor T cell immunity, which not only protected host from challenge by these tumor cells in prevention and therapy in mouse model of lung metastasis, but also prevented tumors development in Gprc5a-ko mouse model of lung tumorigenesis. The lymphocytes from lymph nodes and tumor tissues exhibited greatly enhanced activities of Th1 cells and M1 macrophages. Conclusion Immunization with the ICD dying tumor cells evokes potent tumor-specific T cell immunity, which provides a novel approach for cancer immunotherapy.